Association between glucocorticoid use and all-cause mortality in critically ill patients with heart failure: A cohort study based on the MIMIC-III database - Zhu, Jia-Liang; Hong, Liang; Yuan, Shi-Qi; Xu, Xiao-Mei; Wei, Jian-Rui; Yin, Hai-Yan (Frontiers in Pharmacology, 2023)
Background: Heart failure (HF) is the terminal stage of various heart diseases. Conventional treatments have poor efficacy, and diuretic resistance can present. Previous studies have found that the use of glucocorticoids can enhance the diuretic effect of patients with HF and reduce HF symptoms. However, the relationship between glucocorticoid use and mortality in patients with HF in intensive care units is unclear. Objectives: The aim of this study was to determine the association between glucocorticoid use and all-cause mortality in critically ill patients with HF. Methods: The information on patients with HF in this study was extracted from the MIMIC-III (Medical Information Mart for Intensive Care-III) database. Patients in the glucocorticoid and nonglucocorticoid groups were matched using propensity scores. The Kaplan-Meier method was used to explore the difference in survival probability between the two groups. A Cox proportional-hazards regression model was used to analyze the hazard ratios (HRs) for the two patient groups. Subgroup analyses were performed with prespecified stratification variables to demonstrate the robustness of the results. Results: The study included 9,482 patients: 2,099 in the glucocorticoid group and 7,383 in the nonglucocorticoid group. There were 2,055 patients in each group after propensity-score matching. The results indicated that the nonglucocorticoid group was not significantly associated with reduced mortality in patients with HF during the 14-day follow-up period (HRs=0.901, 95% confidence interval [CI]=0.767–1.059). During the follow-up periods of 15–30 and 15–90 days, the mortality risk was significantly lower in the nonglucocorticoid group than in the glucocorticoid group (HRs=0.497 and 95% CI=0.370–0.668, and HRs=0.400 and 95% CI=0.310–0.517, respectively). Subgroup analyses indicated no interaction among each stratification variable and glucocorticoid use. Conclusion: Glucocorticoid use was associated with an increased mortality risk in critically ill patients with HF.